Early Fractions Learning of 3rd Grade Students in SD Laboratorium Unesa - Elisabet Ayunika Permata Sari; Dwi Juniati; Sitti Maesuri Patahudin (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
Fractions varied meanings is one of the causes of difficulties in learning fractions. These studentsÂ should be given greater opportunities to explore the meaning of fractions before they learn the relationship between fractions and operations on fractions. Although students can shading area represents a fraction, does not mean they really understand the meaning of fractions as a whole. With a realistic approach to mathematics, students are given the contextual issues of equitable distribution and measurements that involve fractions. Keyword:Â fraction meaning, relation of fraction, design research,realistic mathematics education, equitable distribution, measurementÂ DOI: http://dx.doi.org/10.22342/jme.3.1.617.17-28